2013
DOI: 10.1080/01635581.2013.801999
|View full text |Cite
|
Sign up to set email alerts
|

Association of Urinary Phytoestrogen Concentrations with Serum Concentrations of Prostate-Specific Antigen in the National Health and Nutrition Examination Survey

Abstract: Some clinical trials have shown that high phytoestrogen intake may decrease serum concentrations of prostate-specific antigen (PSA), and phytoestrogens may also lower prostate cancer risk. It was the aim of this study to examine the relationship between the serum PSA level and urine phytoestrogen concentration in generally healthy US men. 824 men, 40+ year old without prostate cancer, who participated in the 2001-2004 NHANES surveys, were included in the analysis. The association of total PSA, free PSA, and PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The DXA equipment used was a Hologic QDR 4500A fan beam densitometer [20]. During 1999–2002, NHANES also collected data on muscle strength as measured by the isokinetic strength of the knee extensors using a Kin Com MP dynamometer [21], which enabled the study of both muscle mass and muscle strength. A total of 2,647 men and women, 50 years of age and older, with muscle mass and muscle strength data available from the NHANES 1999–2002, were included in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DXA equipment used was a Hologic QDR 4500A fan beam densitometer [20]. During 1999–2002, NHANES also collected data on muscle strength as measured by the isokinetic strength of the knee extensors using a Kin Com MP dynamometer [21], which enabled the study of both muscle mass and muscle strength. A total of 2,647 men and women, 50 years of age and older, with muscle mass and muscle strength data available from the NHANES 1999–2002, were included in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Muscle strength was established using measurement of the isokinetic strength of the knee extensors at peak force (isokinetic quadriceps strength [IQS]), in newtons [21]. There is evidence that lower extremity strength is associated with physical function, an important component of quality of life [25].…”
Section: Methodsmentioning
confidence: 99%
“…A randomized, double-blind, placebo-controlled study indicated that a daily diet containing four slices of a bread rich in heat-treated soy grits favorably influenced the PSA level and the free/total PSA ratio in patients with prostate cancer, which provides some evidence to support epidemiologic studies claiming that male populations who consume high phytoestrogen diets have a decreased risk of the PSA abnormality and even prostate cancer (56) . Additionally, a cross-sectional study examining the relationship between the serum PSA level and urine phytoestrogen concentration from NHANES 2001-2004 revealed that in generally healthy US men, 40+ years old without a diagnosis of prostate cancer, urinary isoflavone and lignan concentrations were not associated with serum PSA level (57) . Similar results were found among healthy men without HRCs from NHANES 2001-2010 in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that urinary isoflavones concentrations are not associated with serum PSA levels. [ 38 ] It seems that isoflavons may not play an important role on PSA levels reduction in PCa patients or men with clinically identified risk of PCa or healthy men.…”
Section: E Ffects Of S Oy I mentioning
confidence: 99%